2010
DOI: 10.1037/h0100917
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of behavioral activation treatment of anxiety (BATA) in three older adults.

Abstract: This report describes three single-case experimental evaluations of Behavioral Activation Treatment of Anxiety (BATA) applied with a 51-year-old male, a 62-year-old female, and a 53-year-old female, each of whom met DSM-IV criteria for anxiety. Each case was a clinical replication of an initial trial of BATA reported in Turner and Leach (2009). Treatment was delivered in twelve weekly 60-minute individual sessions and evaluated using an A-B-C phase change with repeated measurement design. Decreased scores in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(49 reference statements)
1
5
0
1
Order By: Relevance
“…These studies have demonstrated that participating in 12 weekly 60-minute BA sessions is potentially effective as a stand-alone treatment for older adults' anxiety. 39,40 Similar results have been shown in adult women after participating in a nine-week BA intervention. 38 It is known that stress induces anxiety-like behavior in both humans and animals.…”
Section: Discussionsupporting
confidence: 68%
“…These studies have demonstrated that participating in 12 weekly 60-minute BA sessions is potentially effective as a stand-alone treatment for older adults' anxiety. 39,40 Similar results have been shown in adult women after participating in a nine-week BA intervention. 38 It is known that stress induces anxiety-like behavior in both humans and animals.…”
Section: Discussionsupporting
confidence: 68%
“…For instance, behavioural activation or engagement in pleasurable or distracting activities is often recommended in psychological treatment due to its effectiveness in reducing depression (Benson‐Flórez et al., 2017; Dimidjian et al., 2006; Santiago‐Rivera et al., 2008). Behavioural activation also effectively treats symptoms of anxiety in different age and ethnic populations (Boswell et al., 2017; Taheri et al., 2016; Turner & Leach, 2010). Indeed our findings emphasise that taking time for daily and easy‐to‐implement activities are powerful ways to ameliorate distress during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Además, es recomendable desarrollar un mayor número de estudios con protocolos estándar que incrementen la evidencia de su efectividad para garantizar su validez social (Hernández, Fernández, & Baptista, 2010) y la generalización de sus hallazgos (Sidman, 1980). Además, resulta importante realizar estudios que involucren otro tipo de población que no presente depresión, pues algunos estudios han encontrado que la AC resulta útil en la intervención de otro tipo de problemáticas psicológicas (Turner, & Leach, 2010) e incluso en población no clínica, ayudando a incrementar la participación en actividades de diferente naturaleza (Armento et al, 2012). Dada esta evidencia se recomienda iniciar líneas de investigación que permitan ver los alcances de la activación conductual en otros ámbitos, de tal modo que se pueda ver si resulta mejor la implicación de los individuos en ambientes educativos, organizacionales, sociales, entre otros.…”
Section: Conclusionesunclassified